Geographic distribution and morphological variation in Mimon bennettii (Chiroptera, Phyllostomidae) - Gregorin, Renato; Capusso, Guilherme L. [UNESP]; Furtado, Vanessa R. (FapUNIFESP (SciELO), 2008)
We studied discrete and quantitative data from 88 specimens of the subgenus Mimon previously identified as Mimon bennettii (Gray, 1838) and M. cozumelae Goldman, 1914 from diverse parts of their range. Our data indicate that specimens of Mimon bennetii in Brazil presented geographic variation in morphometrical characters and mosaic variation in qualitative traits. Specimens from the Cerrado biome collected in Brazilian states like Piaui, Tocantins, and Goiás have longer forearms than those distributed in the Atlantic and Amazon forested domains. Based on morphometrics, as showed by t-tests, specimens of M. bennettii from the Brazilian Cerrado resemble phenetically more with M. cozumelae than the M. bennettii from Atlantic Forest. Characters presently used to diagnosis M. cozumelae also were also recorded to M. bennettii in diverse parts of Brazil, making that validity of M. cozumelae questionable based on this kind of traits. This research also updated the geographic distribution to the M. bennettii in Brazil.
Keywords: Atlantic Forest; Cerrado; Distribution; Morphology; Morphometry